2013
DOI: 10.1016/j.survophthal.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

24-hour Intraocular Pressure and Ocular Perfusion Pressure in Glaucoma

Abstract: Abstract. This review analyzes the currently available literature on circadian rhythms of intraocular pressure (IOP), blood pressure, and calculated ocular perfusion pressure (OPP) in patients with openangle glaucoma. Although adequately powered, prospective trials are not available. The existing evidence suggests that high 24-hour IOP and OPP fluctuations can have detrimental effects in eyes with glaucoma. The currently emerging continuous IOP monitoring technologies may soon offer important contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
152
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 118 publications
(151 reference statements)
6
152
0
2
Order By: Relevance
“…4,17 Importantly, 24-hour studies have confirmed that 24-hour IOP monitoring can significantly modify individualized glaucoma care in many glaucoma patients. 18,19 A few 24-hour studies have investigated travoprost efficacy over a period of up to 4 months, [11][12][13]20 but to date no evidence is available for the long-term 24-hour efficacy of travoprost monotherapy in glaucoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,17 Importantly, 24-hour studies have confirmed that 24-hour IOP monitoring can significantly modify individualized glaucoma care in many glaucoma patients. 18,19 A few 24-hour studies have investigated travoprost efficacy over a period of up to 4 months, [11][12][13]20 but to date no evidence is available for the long-term 24-hour efficacy of travoprost monotherapy in glaucoma.…”
mentioning
confidence: 99%
“…Prostaglandin analogues have become a popular firstline therapy option for lowering IOP in POAG owing to their superior 24-hour efficacy, [1][2][3][4][5][6] convenient once-a-day administration, 5 and favorable systemic safety profile. 7 Travoprost is a synthetic prostaglandin F2a analogue that exerts its IOP-lowering effect through the prostaglandin FP receptors situated at the ciliary muscle 8 and the trabecular meshwork.…”
mentioning
confidence: 99%
“…11 Yet, we still know little about the physiology of SC in normal people. As there is IOP fluctuation throughout the whole day, [12][13][14] it is not known if there will be ''morphological fluctuation'' of the SC. Moreover, are there other factors, such as autonomic nervous activity, influencing the morphology of SC in addition to IOP?…”
mentioning
confidence: 99%
“…Does the new drug affect non-IOP parameters (e.g. ocular hemodynamics) that can have an impact on glaucoma [15]? And ultimately, how good is each agent at preserving vision over the long term?…”
Section: Expert Opinionmentioning
confidence: 99%